ADOPSI DIGITAL PAYMENT: - Gusi Putu Lestara Permana; Ni Made Mia Damayanti (UNHI Press, 2022)
The development of the times made the cash payment system gradually switch to digital-based non-cash payments called digital payments. Digital payment users are now dominated by Generation X, Millennials, and Z. However, this is different from the baby boomer generation who were born in 1946-1964. This generation is an individual who is slow and not yet fluent in adopting new technology. This study aims to determine the adoption of the use of digital payments in the baby boomer generation. The object of this research is the baby boomer generation in Denpasar City. The number of samples in this study was 75 respondents. The technique used is purposive sampling and uses multiple regression analysis using SPSS software version 25. The results showed that the perception of usefullnes, ease of use, and security have a positive and significant effect on the behavioral intention of the baby boomer generation to use digital payments